Impact of orange essential oil on enteric methane emissions of heifers fed bermudagrass hay - Jiménez-Ocampo, Rafael; Montoya-Flores, María D.; Pamanes-Carrasco, Gerardo; Herrera-Torres, Esperanza; Arango, Jacobo; Estarrón-Espinosa, Mirna; Aguilar-Pérez, Carlos F.; Araiza-Rosales, Elia E.; Guerrero-Cervantes, Maribel; Ku-Vera, Juan C. (Frontiers in Veterinary Science, 2022)
In this study, the effects of orange essential oil (OEO) on the rumen fermentation, nutrient utilization, and methane (CH4) emissions of beef heifers fed a diet of bermudagrass (Cynodon dactylon) were examined. In vitro incubation experiments were conducted in a completely randomized design with three treatments: control (CTL, no additive), OEO1 (0.25% OEO), and OEO2 (0.5% OEO). A substrate of forage and concentrate in a 70:30 dry matter (DM) ratio was used in all treatments. No changes were observed in rumen pH, proportions of volatile fatty acids, and the acetate:propionate ratio (P > 0.05). The addition of 0.25% OEO resulted in a reduction in CH4 production (mL/g) relative to the control (P < 0.05). An in situ study was conducted with 5 g of total mixed ration (TMR) for 6, 12, 24, 48, and 72 hours of incubation. Potential degradability and effective degradability were not affected by OEO supplementation (P > 0.05). In the in vivo study, six crossbred beef heifers (Bos indicus × Bos taurus) fitted with rumen cannulas were assigned to different treatments in a replicated 3 × 3 Latin square design (21-day periods). Heifers were fed TMR at 2.8% of their body weight with no additive (CTL), 0.25% OEO (OEO1), and 0.5% OEO (OEO2). CH4 production was measured in open-circuit respiration chambers. Reductions in gross energy consumption, apparent total tract digestibility, and rumen valerate concentration were observed in the OEO2 treatment (P < 0.05). Additionally, decreases in CH4 emissions (g/d; P < 0.05) and CH4 (MJ gross energy intake/d; P < 0.05) were observed in response to supplementation of 0.5% OEO compared with the CTL treatment. Thus, inclusion of OEO as a feed additive at 0.5% of the TMR reduced CH4 emissions by 12% without modifying fermentation patterns or dry matter intake in heifers fed bermudagrass hay as a basal ration.